Efektivitas Mediasi Sebagai Alternatif Penyelesaian Perkara Perceraian Di Pengadilan Agama - Haeratun Haeratun; Fatahullah Fatahullah (Faculty of Law, Universitas Pattimura, 2022)
Mediation is an alternative form of dispute resolution that has grown and developed along with the growing human desire to resolve disputes quickly and also to satisfy the litigants. The purpose of the study was to determine and analyze the effectiveness of mediation as an alternative to divorce cases at the Mataram Religious Courts and the Praya Religious Courts NTB. The research method includes the type empirical/socio legal research, while the approach used is a socio legal approach. The results of this study are that the success rate of mediating divorce cases at the Mataram religious court and the Praya religious court is still very low because there are still many mediator judges in the religious court who have not been certified so that they do not have the skills to seek peace for the parties, in addition to inadequate facilities and infrastructure.